William J. Nichols and H. Rosi Song, eds. Toward a Cultural Archive of La Movida. Back to the Future. Madison: Fairleigh Dickinson UP, 2014. - Jorge Gonzalez del Pozo (Studies in 20th & 21st Century Literature, 2016)
Review of William J. Nichols and H. Rosi Song, eds. Toward a Cultural Archive of La Movida. Back to the Future. Madison: Fairleigh Dickinson UP, 2014.
Keywords: la Movida